Performance Analysis Of Trans Patriot Bus Impact Covid-19: Terminal Bekasi - Harapan Indah Route - Amar Mufhdin (Journal of World Conference (JWC), 2021)
As the population of the former city grows, the movement of the people in it increases. Provision of mass transportation or Trans Patriot buses is needed to anticipate the congestion that will occur by providing a cheap, fast and safe bus type that can be an alternative. Therefore, it is necessary to conduct research on the performance and quality of service to determine the level of passenger satisfaction with the performance of the Trans Patriot bus on the Bekasi - Harapan Indah Terminal route. From the comparison of the operational performance of the Trans Patiot buses before Covid 19 and the adaptation of new habits, the Comparison of the performance of the Trans Patriot bus for the Bekasi Terminal - Harapan Indah route before Covid 19 and the adaptation of new habits has increased in load factors, headway, travel time and travel speed, This increase is very good in providing services for Trans Patriot bus users. From the results of the questionnaire service performance level obtained from Trans Patriot bus users for the Bekasi Terminal - Harapan Indah route, which stated that the Trans Patriot bus performance was very good at 9%, good at 33%, good enough at 44%, less good at get 11% and not good at 4% and the level of user satisfaction states Very Satisfied at 9.9%, Satisfied at 41.4%, Quite Satisfied 39.6%, Less Satisfied at 8.9% and Not Satisfied 0.4%. This research is expected to be a reference or material for the Bekasi city government to take a policy so that the performance and service of Trans Patriot buses will increase in reducing congestion in the city of Bekasi.